Pengembangan Media Pembelajaran Berbasis Android Pada Materi Aturan Sinus Dan Cosinus Sebagai Sarana Berlatih Mandiri - Gerin Sukma Tahara (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2021)
The purpose of this research is to develop Android-based learning media on the material of the Sinus and Cosine rules material as an independent practice that valid, effective and practical. The development model used in this research is the Borg and Gall development model. Data collection technique was carried out using a questionnaire sheet. Data collection instrument use validation sheets for media experts and material experts, student questionnaire sheets, and doing exercises on learning media. Data analysis technique in this research is quantitative and qualitative descriptive. The development media had a practice questions and games that contain random numbers. The results of the validation by media experts is 3.53 with a valid category. While the results of the validation by material experts is 3.34 with a fairly valid category. The results of the effectiveness test were obtained from the research subjects of 6 people that the results is 83.33% in the effective category. The practicality test results were obtained from a questionnaire of research subjects is 90% meets a very good criteria. It can be concluded that the Android-based learning media on the Sine and Cosine Rules material as an independent practice is valid, effective and practical.